COMPARATIVE ANALYSIS OF THE NUTRITIONAL COMPOSITION OF Clarias gariepinus FROM A LENTIC AND LOTIC FRESHWATER ECOSYSTEM - EGUN , N.K; OLOWO, U. C.; OMORUWOU, P. E.; OBOH, I. P. (Nigerian Journal of Fisheries, 2025)
Water quality has been considered a major factor in fish meat quality. The objective of the study was to determine the effects of different water quality sources on the nutrient composition of Clarias gariepinus from Ikpoba Reservoir and Owan River. Physico-chemical parameters of water samples, proximate and mineral contents of the fish collected from both locations from February 2018 to January 2019 were determined as outlined by standard methods. Results showed that the Ikpoba Reservoir is highly polluted with low dissolved oxygen content and high nitrate, phosphate, iron, zinc and copper contents; while nitrate, phosphate, iron, zinc and copper contents are low with elevated dissolved oxygen content in Owan River. The moisture, protein, lipid, ash and mineral contents in Clarias gariepinus were significantly (p < 0.01) influenced by the prevailing water conditions of the study locations. Clarias gariepinus obtained from Owan River had moisture (68%), protein (16.52%) and lipid (7.18%) contents that were significantly higher than the moisture (61%), protein (15.15%) and lipid (6.03%) contents in Clarias gariepinus from Ikpoba Reservoir. Protein and lipid contents showed positive correlation with water dissolved oxygen content. Clarias gariepinus obtained from Ikpoba Reservoir has significantly higher contents of ash, iron, zinc, calcium, sodium and copper in comparison to fishes from Owan River. This study has broadened the knowledge on effect of water quality on the nutritional composition of fish meat, thereby assisting in determining the suitability of different aquatic ecosystems for the production of quality fish meat.